Doctrinal and phenomenological opening frames. Routes of Kantian exploration - Heymann, Ezra (Estudios de Filosofía, 2014)
The article is a reflection that presupposes a long journey with Kant’s texts; it provides guidance for reading the philosophical work. First by attending to its incompleteness, as it is part of its nature that we continue to reflect on the problems that it addresses. In the specific case of Kant’s philosophy, it emphasizes the versatility of its fundamental concepts as well as their worldliness.